Differences in perceptual representations in multilinguals’ first, second, and third language - Chen, Donggui; Su, Jingan; Wang, Ruiming (Frontiers in Human Neuroscience, 2024)
Two experiments were conducted to investigate the differences in perceptual representations among multilingual individuals. In Experiment 1, the immediate sentence-picture verification paradigm was used to investigate perceptual representations in the working memory stage. The results suggest a match effect within the first language (Cantonese), but not within the second language (Mandarin) or the third language (English), showing perceptual representations only in first language comprehension. In Experiment 2, the delayed sentence-picture verification paradigm was used to investigate perceptual representations in long-term memory. Similarly, the results suggest a match effect within the first language (Mandarin), but not within the second language (English). The findings of both experiments suggest that the first language was perceptually represented, regardless of whether it was Cantonese or Mandarin, regardless of the processing in working memory or long-term memory. No evidence was found for perceptual representations in the later-learned languages, regardless of high or low proficiency. Our study has implications for theories of language comprehension and embodied cognition.